2023
DOI: 10.46799/ijssr.v3i5.384
|View full text |Cite
|
Sign up to set email alerts
|

Literature Study: The Role Of Accountants In Reporting Environmental, Social, And Governance Information

Abstract: The purpose of this study is to get an overview of the role of accountants in terms of existing literature in relation to information related to Environmental Social Governance (ESG). In addition to the role of accountants, the role of the audit committee is also needed as an independent party in order to minimize the opportunities for accountants and management to commit fraud. Methods: The research method in this article is qualitative research with a literature review approach obtained from articles and jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Professional accountants play a significant role in ensuring social responsibility practices and enterprises' sustainable development strategies. Ramadhan et al (2023) found that accountants play an important role in ensuring businesses and projects run more environmentally friendly and sustainable, following ESG principles reflected in the company's financial reporting. Nguyen et al (2019) found that accountants' qualifications positively enhance modern management accounting practices adoption in Vietnamese enterprises.…”
Section: Accountants' Levels (Al)mentioning
confidence: 99%
“…Professional accountants play a significant role in ensuring social responsibility practices and enterprises' sustainable development strategies. Ramadhan et al (2023) found that accountants play an important role in ensuring businesses and projects run more environmentally friendly and sustainable, following ESG principles reflected in the company's financial reporting. Nguyen et al (2019) found that accountants' qualifications positively enhance modern management accounting practices adoption in Vietnamese enterprises.…”
Section: Accountants' Levels (Al)mentioning
confidence: 99%